Muhammadiyah Values as a Moderator of the Effects of Entrepreneurial Orientation, Financial Literacy, and Digital Leadership on University Performance - Acep Suherman; Sri Widyastuti; Nurmala Ahmar (Academic Bright Collaboration, 2026)
Purpose – This study examines how entrepreneurial orientation and financial literacy influence perceived university performance and investigates the mediating role of digital leadership and the moderating role of Muhammadiyah values. The study addresses the limited integration of strategic capabilities and religio-cultural values in higher education performance models. Methods – A quantitative cross-sectional design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 456 leaders of Muhammadiyah and Aisyiyah universities across Indonesia through structured questionnaires. Findings – Entrepreneurial orientation, financial literacy, and digital leadership each have positive and significant effects on perceived university performance. Digital leadership partially mediates the relationships between entrepreneurial orientation and performance, as well as between financial literacy and performance. Muhammadiyah values strengthen the relationship between digital leadership and performance, weaken the relationship between financial literacy and performance, and do not significantly moderate the relationship between entrepreneurial orientation and performance. Research implications – The cross-sectional design and reliance on self-reported leadership perceptions limit causal inference and may introduce common method bias. Future research should employ longitudinal or multilevel designs and incorporate objective performance indicators. Originality – This study demonstrates that religio-cultural institutional values act as differentiated boundary conditions in higher education, selectively strengthening, weakening, or not affecting capability–performance relationships